2013
DOI: 10.1155/2013/135731
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Analysis of Power Grids Using Modified Centrality Measures

Abstract: The aim of this paper is to propose modified centrality measures as a tool to identify critical nodes before a vulnerability analysis is performed in an electrical power grid. Pair dependency centrality is weighted using the grid active power flow, and this becomes the basis to define closeness and betweenness of its nodes, and hence to identify the most critical ones. To support the idea of using modified centralities, four power grids are tested to be either exponential or scale-free. To evaluate the proposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
0
12
0
3
Order By: Relevance
“…Important buses are defined as they have an important impact on the characteristic and the reliability of power grid. Similar to [19][20][21][22], the centrality measure technique is also used to obtain the relative importance of nodes in the network. In this study, we improve the formula to calculate the importance of bus in power system through an index called Observation Degree Index (ODI).…”
Section: Modified Weighted Adjacent Matrixmentioning
confidence: 99%
“…Important buses are defined as they have an important impact on the characteristic and the reliability of power grid. Similar to [19][20][21][22], the centrality measure technique is also used to obtain the relative importance of nodes in the network. In this study, we improve the formula to calculate the importance of bus in power system through an index called Observation Degree Index (ODI).…”
Section: Modified Weighted Adjacent Matrixmentioning
confidence: 99%
“…Bompard et al discussed several well‐known assumptions of the CN theory with reference to characteristics of the power grid . Gutierrez et al modified centrality measures including closeness and betweenness centrality to identify the vulnerable nodes in the power grid …”
Section: Introductionmentioning
confidence: 99%
“…20 Gutierrez et al modified centrality measures including closeness and betweenness centrality to identify the vulnerable nodes in the power grid. 21 However, in contrast to traditional CNs, nodes in the power grid are electrically coupled to their neighbor nodes, ie, nodes will occur transient oscillation when its neighbor nodes fail, or oscillation will be diffused through the transmission line leading to a cascading failure of the power system. Zhang et al assumed the initial load node as the linear summation of its degree and the sum of its neighbors' degrees, and local load redistribution is used to study the vulnerability of power grid when a node is attacked.…”
Section: Introductionmentioning
confidence: 99%
“…For the power grids with electrical properties, scholars have proposed some node importance evaluation methods. Gutierrez et al [14] identified the critical nodes in an electrical power grid by introducing the modified centrality measures including closeness and betweenness. Luo et al [15] presented an index called transmission betweenness to identify the key transmission links and applied the clustering algorithm to obtain the partition sections from the key transmission links.…”
Section: Introductionmentioning
confidence: 99%